Deadliest tumor of oral cavity: A rare case of intra oral malignant melanoma - Nunsavathu Purnachandrarao Naik; Alaparthi Ravi Kiran; Yalamanchili Samata; Ambaldhage Vijay Kumar (Wolters Kluwer Medknow Publications, 2014)
Malignant melanoma is a rare tumor arising from the uncontrolled growth of melanocytes found in the basal layer of the epithelium. Although cutaneous malignant melanoma is the third most common malignancy of the skin, it accounts only for 3-5% of all dermal malignancies. Primary malignant melanoma of the oral mucosa is extremely rare, accounting for only 0.2-8% of all malignant melanomas. The incidence is slightly higher in males while others report a higher incidence in females. In the oral cavity, 80% of the cases occur in the maxilla with the prevalence of the hard palate or combined with the gingival or alveolar ridge. In this paper, we present a rare case of a 47-year-old female patient who reported with completely asymptomatic, pigmented growth in the maxillary anterior region.